Comparison of oral microbiome diversity between children and young adults in Korea - Park, Jung Hwa; Kim, Si Yeong; Chung, Jin (International journal of oral biology, 2024)
The oral microbiome plays a vital role in maintaining oral and overall health and affects immune responses, digestion, and pathogen suppression. While most studies focus on age groups prone to specific conditions, such as dental caries in children or periodontal disease in older adults, limited data exist on preschool-aged children and young adults. This study investigates the composition and diversity of the oral microbiome between these age groups for enhanced understanding of a healthy oral microbiome. Microbial samples from the supragingival regions of 41 children and 31 young adults in Korea were analyzed using 16S rRNA gene sequencing. Alpha and beta diversity were assessed, and linear discriminant analysis effect size (LEfSe) identified taxa with significant differences in abundance between the groups. No significant differences in alpha diversity were observed between children and young adults however, beta diversity analysis revealed notably compositional differences. At the phylum level, Firmicutes were more abundant in children, whereas Actinobacteria were more prevalent in young adults. Genera such as Veillonella and Lautropia were more abundant among children, whereas Haemophilus and Rothia were more common among young adults. LEfSe analysis identified Veillonella rogosae and Lautropia mirabilis as more abundant in children, whereas Haemophilus parainfluenzae and Rothia dentocariosa were more prevalent in young adults. The observed differences suggest that children’s microbiomes are associated with biofilm development, while young adults’ microbiomes involve biofilm maturation and immune modulation. These findings highlight the age-related shift in oral microbiome composition, emphasizing the importance of monitoring these changes to support long-term oral health.